2013
DOI: 10.1021/cn400024q
|View full text |Cite
|
Sign up to set email alerts
|

Olive-Oil-Derived Oleocanthal Enhances β-Amyloid Clearance as a Potential Neuroprotective Mechanism against Alzheimer’s Disease: In Vitro and in Vivo Studies

Abstract: Oleocanthal, a phenolic component of extra-virgin olive oil, has been recently linked to reduced risk of Alzheimer's disease (AD), a neurodegenerative disease that is characterized by accumulation of β-amyloid (Aβ) and tau proteins in the brain. However, the mechanism by which oleocanthal exerts its neuroprotective effect is still incompletely understood. Here, we provide in vitro and in vivo evidence for the potential of oleocanthal to enhance Aβ clearance from the brain via up-regulation of P-glycoprotein (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
205
0
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 228 publications
(215 citation statements)
references
References 45 publications
8
205
0
2
Order By: Relevance
“…Others have demonstrated that EVOO has direct antioxidant property by acting as scavenger of reactive oxygen species and blocker of free radical formation in cellular system 26. On the other hand, animal model studies have provided evidence for a beneficial effect of EVOO on behavior as well as brain amyloidosis 27. However, since these models do not develop the second most important hallmark lesion of the AD brain pathology, it remains to be investigated whether or not EVOO has a beneficial effect on the development of tau neuropathology.…”
Section: Discussionmentioning
confidence: 99%
“…Others have demonstrated that EVOO has direct antioxidant property by acting as scavenger of reactive oxygen species and blocker of free radical formation in cellular system 26. On the other hand, animal model studies have provided evidence for a beneficial effect of EVOO on behavior as well as brain amyloidosis 27. However, since these models do not develop the second most important hallmark lesion of the AD brain pathology, it remains to be investigated whether or not EVOO has a beneficial effect on the development of tau neuropathology.…”
Section: Discussionmentioning
confidence: 99%
“…OLC elicits this irritation via the same mechanisms as ibuprofen (Peyrot des Gachons et al, 2011;Bennett & Hayes, 2012) and mimics the anti-inflammatory activities of ibuprofen via the inhibition of COX-1 and COX-2 enzymes at almost equimolar concentrations (Beauchamp et al, 2005;Lucas et al, 2011). Recently, several other potentially health promoting activities of OLC were described (Parkinson & Keast, 2014), such as 1) the enhancement of amyloid-β clearance from the brain (Abuznait, Qosa, Busnena, El Sayed & Kaddoumi, 2013) and the modulation of the fibrillization of tau protein (Monti, Margarucci, Riccio & Casapullo, 2012), both important mechanisms in neurodegenerative diseases;…”
Section: Introductionmentioning
confidence: 99%
“…Thus, isolation of OLC from natural sources (olive oil, olive oil pomace, olive leaves or olive oil mill waste water) is an important option. Previous methods are quite laborious and time-consuming due to the use of column chromatography and/or preparative HPLC (Paiva-Martins & Gordon, 2001;Agalias et al, 2007;Khanal et al, 2011;Abuznait, Qosa, Busnena, El Sayed & Kaddoumi, 2013). In addition, for OLC keto-enol tautomerism and decomposition upon exposure to oxygen and light has been reported (Caruso, Colombo, Patelli, Giavarini & Galli, 2000;Cicerale, Conlan, Barnett & Keast, 2013), which has to be considered in the development of efficient isolation procedures.…”
Section: Introductionmentioning
confidence: 99%
“…A study conducted on cultured bEnd3 mice brain endothelial cells and C57BL/6 mice suggests that intraperitoneal administration of OLC to mice can increase the clearance of 125 I-A"(1-40) from the brain by up-regulating both A" degrading enzymes (Neprilysin and Insulin degrading enzyme) and A" transporters (P-glycoprotein and LDL receptor related protein-1) at the Blood Brain Barrier (BBB) (Abuznait et al 2013). These effects are highly relevant because the expression of such transporters declines with ageing and in AD, possibly contributing to amyloid accumulation in the brain parenchyma (Silverberg et al 2010;Vogelgesang et al 2004).…”
Section: Oleocanthalmentioning
confidence: 99%